Pancreatic ductal adenocarcinoma progression is restrained by stromal matrix - Jiang, Honglin; Torphy, Robert J.; Steiger, Katja; Hongo, Henry; Ritchie, Alexa J.; Kriegsmann, Mark; Horst, David; Umetsu, Sarah E.; Joseph, Nancy M.; McGregor, Kimberly; Pishvaian, Michael J.; Blais, Edik M.; et al. (The journal of clinical investigation, 2020)
Desmoplasia describes the deposition of extensive extracellular matrix and defines primary pancreatic ductal adenocarcinoma (PDA). The acellular component of this stroma has been implicated in PDA pathogenesis and is being targeted therapeutically in clinical trials. By analyzing the stromal content of PDA samples from numerous annotated PDA data sets and correlating stromal content with both anatomic site and clinical outcome, we found PDA metastases in the liver, the primary cause of mortality to have less stroma, have higher tumor cellularity than primary tumors. Experimentally manipulating stromal matrix with an anti–lysyl oxidase like-2 (anti-LOXL2) antibody in syngeneic orthotopic PDA mouse models significantly decreased matrix content, led to lower tissue stiffness, lower contrast retention on computed tomography, and accelerated tumor growth, resulting in diminished overall survival. These studies suggest an important protective role of stroma in PDA and urge caution in clinically deploying stromal depletion strategies.
Gesehen am 11.01.2021